Insulin‐Like Growth Factor Promotes Cardiac Lineage Induction In Vitro by Selective Expansion of Early Mesoderm. (June 2014) - Engels, Marc C.; Rajarajan, Kuppusamy; Feistritzer, Rebecca; Sharma, Arun; Nielsen, Ulrik B.; Schalij, Martin J.; de Vries, Antoine A.F.; Pijnappels, Daniël A.; Wu, Sean M.
Abstract: A thorough understanding of the developmental signals that direct pluripotent stem cells (PSCs) toward a cardiac fate is essential for translational applications in disease modeling and therapy. We screened a panel of 44 cytokines/signaling molecules for their ability to enhance Nkx2.5 + cardiac progenitor cell (CPC) formation during in vitro embryonic stem cell (ESC) differentiation. Treatment of murine ESCs with insulin or insulin‐like growth factors (IGF1/2) during early differentiation increased mesodermal cell proliferation and, consequently, CPC formation. Furthermore, we show that downstream mediators of IGF signaling (e.g., phospho‐Akt and mTOR) are required for this effect. These data support a novel role for IGF family ligands to expand the developing mesoderm and promote cardiac differentiation. Insulin or IGF treatment could provide an effective strategy to increase the PSC‐based generation of CPCs and cardiomyocytes for applications in regenerative medicine. Stem Cells 2014;32:1493–1502